What happens on Wednesdays - Jenkins, Emily, 1967- (Farrar, Straus and Giroux, 2007)
A child describes every event that occurs on a Wednesday, from waking up while it is still dark out and deciding it is not a kissing day, through a half-day of school, to snuggling into bed at night.